Guillain-Barré Syndrome in Egypt: Diagnostic Challenges and Subtype Evolution Over Time - Elghzzawy, Dena; Farouk, Ayatallah; Abdelkhalek, Ahmed; Elmenshawi, Ibrahim (International Journal of Statistics in Medical Research, 2025)
Background: Guillain-Barré Syndrome (GBS) is the leading cause of acute flaccid paralysis worldwide, with diverse clinical and electrophysiological presentations. Regional variation in GBS subtypes exists, but limited data are available from Arab countries, particularly Egypt. Objective: This study aimed to characterize clinical features, neurophysiological patterns, and disability outcomes among Egyptian GBS patients and evaluate changes in electrophysiological subtypes over time. Methods: A prospective observational study was conducted on 49 adult patients diagnosed with GBS and admitted to Mansoura University Hospitals between May 2022 and May 2025. Clinical data, disability scores (Hughes, INCAT, mEGOS, MRC), and electrophysiological findings were collected within the first two weeks of symptom onset and repeated before discharge. Electrophysiological subtyping was performed using Rajabally’s criteria at initial and repeat testing. Results: The cohort had a median age of 50 years; 59.2% were male. Upper respiratory tract infections were the most common preceding illness (55.1%). Sensorimotor deficits were the predominant presentation (89.8%), with cranial nerve involvement observed in 28.6% and autonomic dysfunction in 20.4%. Most patients received plasma exchange, and 22.4% required additional immunotherapy. Initial electrophysiological studies were inconclusive in 37.4%, but follow-up improved diagnostic yield to 93.7%. Electrophysiological reclassification occurred in 54.1%, with cases shifting between axonal and demyelinating patterns. At follow-up, AIDP was slightly more prevalent (52%) than axonal forms (41.6%). Functional scores (Hughes, INCAT, MRC) improved significantly within one month, with >65% achieving favorable outcomes. Conclusion: Serial neurophysiological assessment enhances diagnostic accuracy in early GBS subtypes classification, with substantial shifts occurring between initial and follow-up studies. A high proportion of Egyptian GBS patients presented with severe disability but showed marked improvement by the fourth week.